Giving sense and making choices: supporting ethnographic and discursive approach to the news - Correia, João Carlos (2020)
The need to direct our attention to different events in a permanent flow is the reverse of the ambition of universality that motivates journalism. Journalists cannot turn their attention to all events as if they all have the same relevance. Frames and typifications are procedures used by professionals to establish the relevance of issues. However, this relative relevance is, often, established at the expense of diversity and openness. We stand for a research project in journalism studies, drawing on plural contributions (Discourse Analysis Phenomenology, Interactionism and Ethnography) that help professionals to produce an inclusive news reporting